Environmental and enviroeconomic analyses of two different turbofan engine families considering landing and take-off (LTO) cycle and global warming potential (GWP) approach - Aygun, Hakan; Caliskan, Hakan (Pergamon-Elsevier Science Ltd, 2021)
In this study, environmental and enviroeconomic analyses regarding two different turbofan engine families that are commonly used in commercial aircrafts are carried out at Landing and Take-Off (LTO) cycle involving takeoff, climb-out, approach and idle phases. For this aim, HC, CO, NOX and CO2 emissions of family 1 (F1) and family 2 (F2) engines are taken into consideration over the course of LTO cycle based on International Civil Aviation Organization (ICAO) emission database. The average thrust values of these engines are 115.12 kN for F1 engines and 123.77 kN for F2 engines. Global Warming Potential (GWP) and enviroeconomic cost factor (ECF) for the each engine are calculated. Also, to predict GWP and ECF parameters, these metrics are modelled based on by-pass ratio and overall pressure ratio. According to the results of the study, the average GWP value of F1 and F2 engines are obtained as 2256.17 kg_CO2/day_cycle and 1779.02 kg_CO2/day_cycle, respectively. On the other hand, the average enviroeconomic cost factor (ECF) of F1 and F2 engines are computed as 261.71 Euro/day_cycle and 206.36 Euro/day_cycle, respectively. Finally, accuracy of GWP model is achieved with R2 = 0.9956 for F1 engines and R2 = 0.9664 for F2 engines. The relatively low R2 of the model for F2 engines could be attributed to effects of different types of the combustor. It is seemed that the present analysis allows to predict the average environmental effect and economic cost of the aircraft engines in service.
Keywords: Environmental assessment; Aircraft engines; LTO cycle; Turbofan engine parameters